Entrepreneurial Leadership, Entrepreneurial Orientation, Organizational Effectiveness and Their Relationships Towards Firm Performance - Rudi Suhendi; Soebowo Musa (Emerging Markets : Business and Management Studies Journal, 2022)
This study is a cross-sectional descriptive & confimatory study that analyzes the Indonesian heavy equipment industry. Therefore, the results only represent the condition of the industry at a certain point in time the research was conducted, unlike longitudinal data. Another implication is that this research cannot determine causality between constructs and can only represent the current condition. The construct that the author measures is entrepreneurial leadership (EL), entrepreneurial orientation (EO), organizational effectiveness (OE) and Firm performance (FP). FP is a relevant construct in strategic management research and is often used as the dependent variable. Despite this relevance, there is almost no consensus on its definition, dimensions and measurement, what is limiting progress in research and understanding of the concept. Successful FP operating in dynamic and changing environments have the ability to reach out and explore new sights. When the current conditions for new employee recruitment have been reduced, even every year there are no additional new employees, expenses, optimization & additional work jobs for each employee, etc. Possibly with this, I as the author would like to examine current in the company whether they have EL, EO, OE to improve FP, where employees understand and apply how Risks of risk and uncertainty as well as being proactive in maintaining the company's growth, so that the company can survive in a dynamic business situation. And for this study the author also wants to clarify that EL, EO, OE and FP are their have relationship have a positive effect for each others.